Synthesis Of Immobilized Nano-Tio2 For Photocatalytic Degradation Of Phenol - Zainudin, Nor Fauziah (2010)

(untitled)
The presence of phenol in wastewater represents a significant environmental problem. Due to some drawbacks in conventional wastewater treatment, photocatalysis provides an interesting alternative. Immobilized nano-TiO2 photocatalyst was successfully synthesized using modified sol gel method and was investigated for photocatalytic degradation of phenol in a batch reactor. The synthesized photocatalyst composition was developed using nano-TiO2 as photoactive sites and zeolite as adsorbent, all immobilized onto support using binder. A series of experiments were conducted to investigate the influence of Degussa P25 in alkoxide sol and the suitable type of each component for the role of immobilized nano-TiO2 catalyst components. TiO2 based adsorbent photocatalyst which using the concept adsorbent concentrate target compound near TiO2 was applied to overcome the drawback of the high energy needed of TiO2 application. The purpose of using immobilized catalyst is to prevent the need of costly separation after treatment and due to the ability of reused catalyst.